Ubiquitous networking : third International Symposium, UNet 2017, Casablanca, Morocco, May 9-12, 2017, Revised selected papers /: third International Symposium, UNet 2017, Casablanca, Morocco, May 9-12, 2017, Revised selected papers. (2017) - Unknown
No abstract available